The Role Of Enterprise Net Works In The Internationalization Of Smes With Referring To Some Networks In Algeria (Journal of Namibian Studies : History Politics Culture, 2024)
This study addresses the role of enterprise networks in internationalizing the activities of small and medium-sizedenterprises by definingthis type of enterprises and identifying the main benefitsthat networks can achieve in supporting the presence of small and medium-sizedenterprises in international markets. The studyalsoprovides a historicaloverview of the emergence and evolution of networks, and discusses the dimensions of enterpriseinternationalization in an attempt to identify the key challenges thatneed to beaddressed in case there are plans to expand into international markets. The study clarifies thatthese challenges can beovercome by clustering small and medium-sizedenterprisesinto groups or networks withexperience and knowledge of foreignmarkets, and it points out some of these networks in Algeria, focusing on their positives despitebeing a relativelyyoungexperienceso far.